One year of high-frequency monitoring of groundwater physico-chemical parameters in the Weierbach experimental catchment, Luxembourg - K. N. van Zweel; K. N. van Zweel; L. Gourdol; J. F. Iffly; L. Léonard; F. Barnich; L. Pfister; E. Zehe; C. Hissler (Earth System Science Data)
The critical zone (CZ) is the skin of the Earth, where rock, water, air, and life interact, playing a pivotal role in sustaining ecological processes and life-supporting resources. Understanding these interactions, especially in forested headwater catchments, is essential to manage water resources, predict environmental responses, and assess human impacts. Here, we present a novel dataset from the Weierbach experimental catchment in Luxembourg, derived from a year-long high-frequency monitoring campaign focused on groundwater physico-chemical parameters.